Manajemen Emboli Paru di Intensive Care Unit (ICU) - Redjeki, Ike Sri; Satrio, Wijanarko (Majalah Anestesia dan Critical Care, 2014)
Emboli paru merupakan komplikasi utama tromboemboli vena (VTE). Emboli paru termasuk dalam kegawatan kardiovaskular. Tersumbatnya pembuluh darah arterial paru dapat mengancam kehidupan disertai kegagalan ventrikel kanan yang dapat reversibel. Diagnosis (PE) yaitu adanya gejala umum dan tanda-tanda klinis seperti hipoksia, takipnea, dan takikardia. Di ICU, sebagian besar pasien memerlukan sedasi dan ventilasi mekanis sehingga manifestasi klinis tidak khas dan biasanya atipikal. Baku emas diagnosis PE adalah ditemukannya sumbatan pada angiografi paru. Diagnosis dan tatalaksana suportif menjadi sangat penting mengingat mortalitasnya yang tinggi. Oksigenasi, intubasi, dan ventilasi mekanik diperlukan untuk kegagalan pernafasan. Terapi vasopressor harus dipertimbangkan jika tekanan darah masih rendah. Terapi antikoagulan memainkan peran penting dalam pengelolaan pasien PE. Heparin dan low molecular weight heparin dapat diberi di awal. Pada kasus yang berat mungkin memerlukan trombolisis dengan obat-obatan seperti tissue plasminogen activator (tPA) atau mungkin memerlukan intervensi bedah melalui thrombectomy paru. Kata kunci: Antikoagulan, emboli paru, tromboemboli vena Pulmonary embolism is the major complication of venous thromboembolism (VTE). Pulmonary embolism is a cardiovascular emergency. By occluding the pulmonary arterial bed it may lead to acute life threatening but potentially reversible right ventricular failure. The diagnosis of (PE) is usually suspected by the presence of common symptoms and clinical signs include hypoxia, tachypnea, and tachycardia. However in ICU, the most of patients required sedation and mechanical ventilation. The clinical manifestations is usually atypical. While the gold standard for diagnosis is the finding of a clot on pulmonary angiography, once it is suspected, a diagnostic plan and supportive measures are essential. Oxygen supplementation, intubation, and mechanical ventilation are instituted as necessary for respiratory failure. Vasopressor therapy should be considered if the blood pressure is not rapidly restored. Anticoagulant treatment plays a pivotal role in the management of patients with PE. Heparin, low molecular weight heparins is administered initially. Severe cases may require thrombolysis with drugs such as tissue plasminogen activator (tPA) or may require surgical intervention via pulmonary thrombectomy. Key words: Anticoagulant, pulmonary embolism, venous thrombus Reference Zochios V, Keeshan A. Pulmonary embolismin the mechanically-ventilated critically ill patient: is it different? The intensive care societty 2013. 2013;14:36–44. Marino P, penyunting. Venous thromboembolism. Philadelphia: Lipincott Williams Wilkins; 2007. Williams M, Aravindan N, Wallace M. Venous thromboembolism in the intensive care unit. Crit Care Clin 2003;19:185–207. Adam T, Arnaud P, Konstantinides S, Agnelli G, Galle N, Pruszczyk P. Guidelines on the diagnosis and management of acute pulmonary embolism. European Heart Journal. 2008;29:2276–315. Forgione A. Managing patients with suspected pulmonary embolism. JAAPA. 2006;19:22–8. Stoelting K, Dierdorf S, Penyunting. Deep vein thrombosis and pulmonary embolism. Philadelphia; 2002. Bahloul M, Chaari A, Kallel H, Abid L, Hamida C, Dammak dkk. Pulmonary embolism in intensive care unit: predictive factors, clinical manifestations and outcome. Ann Thorac Med 2010;5:97–103. Waldmann c, Vincent JL. Pulmonary Embolism the future, Optimising the prevention of PE in the critically ill patient. Journal of the intensive care society. 2014;15:2–16.